Scaling access to index-based insurance for more productive agriculture: Experiences, lessons learned and perspectives - Ouedraogo, Issa; Sarr, Yassine; Omar, Sow; Chilambe, Pedro (2023)
The CGIAR Research Initiative on Climate Resilience (ClimBeR) addresses critical challenges smallholder farmers face in Senegal and similar regions due to climate change. The collaboration with the National Agricultural Insurance Company (CNAAS) to promote the uptake of agricultural insurance, particularly index-based insurance, is a noteworthy strategy.